Starlikeness and close-to-convexity involving certain differential inequalities - SHERGILL, Kuldeep Kaur; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In the present paper, we study certain differential inequalities involving meromorphic functions in the open unit disk and obtain certain sufficient conditions for starlikeness and close-to-convexity of meromorphic functions. Mathematics Subject Classification (2010): 30C45, 30C80. Received 06 April 2021; Accepted 11 October 2022